Peranan Penyuluh Pertanian dan Kemampuan Teknis Perempuan pada Usahatani Jagung dalam Mendukung Terwujudnya SDGs di Kecamatan Pujut Lombok Tengah - Hayati, Hayati; Sahidu, Arifuddin; Muktasam, Muktasam; Yanuarti, B. Yulfia Elsa Dewi (Universitas Mataram, 2024)
The existence of agricultural instructors is very important for women farmers to improve women's technical abilities in corn farming on dry land and support the realization of SDGs in the field of education in Pujut District, Central Lombok. The aim of this research is to analyze the role of agricultural instructors and the level of technical abilities of women farmers in corn farming as well as the correlation between the role of agricultural instructors and the level of technical abilities of women farmers. Data collection for this descriptive research was collected using interview techniques using questionnaires from 60 respondents in Mertak Village and Sukadana Village. The collected data was processed and analyzed using descriptive and inferential statistics, namely Spearman's Rank Correlations. The results of this research are that the level of technical ability of women farmers in corn farming is relatively high, the role of agricultural instructors is quite high, and there is a strong correlation between the role of instructors and the level of women's technical abilities.